2011
DOI: 10.5171/2011.606307
|View full text |Cite
|
Sign up to set email alerts
|

Call Centers Performance An Application of Structuration Theory

Abstract: The academic field of individual performance is concerned with a large range of multifaceted questions regarding the prediction of individual performance, the assessment issue, or the enhancement and the keeping of a performance value. Current debates have emerged in call centers context. Based on structuration theory, this paper tries to understand the process that leads to individual performance. A case study based on half structured interviews is made at "Téléperformance". Results show that there are three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…This same structural framework has been applied broadly to such settings as community health practices, information technology, geography, social psychology, organizational science, and management research and we suggest that there is much potential in applying it to the university environment (see Oppong, 2014;Pozzebon & Pinsonneault, 2005;Kort & Gharbi, 2011;Kristiansen, 2009;Asante-Sarpong, 2007;Albano, Masino & Maggi, 2010;den Hond, Boersma, Heres, Kroes van Oirschot, 2012;Whittington, 1992).…”
Section: Navigating the Change: Overcoming Resistance Structuration T...mentioning
confidence: 87%
“…This same structural framework has been applied broadly to such settings as community health practices, information technology, geography, social psychology, organizational science, and management research and we suggest that there is much potential in applying it to the university environment (see Oppong, 2014;Pozzebon & Pinsonneault, 2005;Kort & Gharbi, 2011;Kristiansen, 2009;Asante-Sarpong, 2007;Albano, Masino & Maggi, 2010;den Hond, Boersma, Heres, Kroes van Oirschot, 2012;Whittington, 1992).…”
Section: Navigating the Change: Overcoming Resistance Structuration T...mentioning
confidence: 87%
“…One of the research domains that have appropriated Giddens' theory is Information Systems Research (ISR). For instance, Jones and Karsten (2003) and Kort and Gharbi (2011) indicate that structuration theory has been greatly employed as theoretical framework in ISR, though in its original formlation, information systems was never mentioned. According to Pozzebon andPinsonneault (2005, cited in Kort &Gharbi, 2011, p. 6), …the aim of structuration theory in the IS field is to provide theoretical approach that helps the understanding of the interaction of user and information technology, the implications of these interactions and the way to control their consequences.…”
Section: Towards An Integrated Model Of Human Actions and Conditionsmentioning
confidence: 99%
“…In their study on the performance of call centre workers in Tunisia, for example, Kort and Gharbi (2011) employed structuration theory as the framework to guide the research method. They reported that (1) agent features such as motivation, role perception, stress, personality, and a host of others, (2) technological structures such as tools and equipment and (3) non-technological structures such as organizational structure, performance management system, task characteristics, work conditions, and others together determine the level of performance.…”
Section: Towards An Integrated Model Of Human Actions and Conditionsmentioning
confidence: 99%